FUNGSI JAMINAN DALAM PEMBIAYAAN MUSYARAKAH (STUDI PADA PT BANK KALSEL SYARIAH CABANG BANJARMASIN) - Syarqawie, Fithriana; Syaifurrahman, Syaifurrahman (Islamic Economics and Business Faculty of UIN Antasari, 2014)
Basicly Musyarakah in fiqh muamalah is agreement of trust (amanah), which each of partners be rialiable with their own partner that have agreement with them, then in agreement of musyarakah each of partners do not allowed to ask for assurance to other partners. This research uses field research method by directly interviews the authorities of PT Bank Kalsel Syariah Banjarmasin Branch. The result of the procedure of musyarakah finance which is given by PT Bank Kalsel Syariah Banjarmasin Branch is a coorperation agreement between the bank and the clients where each of partners gives the contribution of fund and work in undertaking productive business. The profit result divide based on nisbah that has been agreed and one of the partners can ask the more pofit based on their works and the loss devides proportionally based on the fund that had been deposited by each of partners. The client is asked to include the additional material wealth assurance that worth of the price as a serious prove and responsible reflection of the clients to undertake a coopertion and also as bank media in undertaking the principle of carefulness in giving the finance.